Synthesis and electrical properties of CaO doped BZT lead free piezo ceramics. (8th April 2016) - Chandraiah, M.; Sahoo, B.; Panda, P. K.
Abstract: Effect of CaO on ferroelectric, dielectric, piezoelectric properties of Barium Zirconate Titanate (BZT) lead free piezo ceramics was studied. The powders were prepared by mixed-oxide route, calcined at 1000°C for 4 h. XRD patterns of the calcined powders show phase pure perovskite structure. The calcined powders were de-agglomerated, granulated, pressed into pellets and sintered at 1150°C for 3 h. Scanning Electron Microscopy (SEM) studies of thermally etched sintered pellets show sub-micron sized grains for undoped BZT which increases up to 5–8 μm sized for 0.015 mol CaO doped BZT. Energy Dispersive X-ray analysis (EDS) of CaO doped BZT sample confirms the presence of dopants very close to their stoichiometric compositions. The piezoelectric charge constant (d33 = 248 pC/N), dielectric constant (K = 2521) and remnant polarization (Pr = 4.22 μC/cm 2 ) were maximum for BZT samples containing 0.015 mole of CaO.